Effect of Position-Based Dosing Strategy for Metaraminol on Neonatal Acid–Base Status During Elective Caesarean Delivery: A Noninferiority Randomised Controlled Trial - Liu T; Jiang H; Xu C; Li L; Zhang H; Feng Y (Drug Design, Development and Therapy)
Tianyu Liu,1,* Hua Jiang,1,* Chao Xu,1,2,* Lei Li,3 Hong Zhang,1 Yi Feng1 1Department of Anaesthesiology, Peking University People’s Hospital, Peking, People’s Republic of China; 2Department of Anaesthesiology, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 3Suzhou Wujiang District Center for Disease Control and Prevention, Suzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Zhang; Yi Feng, Department of Anesthesiology, Peking University People’s Hospital, 11 Xizhimen South Street, Xicheng District, Beijing, People’s Republic of China, Tel +86-13601083503 ; +86-13311281808, Email zhangh_18@sina.com; doctor_yifeng@sina.comBackground: The 15° left tilt position during caesarean delivery has been recommended by guidelines for many years, but recent studies have questioned the clinical benefit of left tilt position. We hypothesize that using a higher starting dose of metaraminol in the supine position will result in a non-inferior umbilical arterial pH, compared to the 15° left tilt position.Methods: Healthy women undergoing elective caesarean delivery were randomized to the supine position (n = 62) or 15° left tilt position (n = 62) after spinal anaesthesia (0.5% bupivacaine 9 mg). Different starting doses of metaraminol infusion were initiated at 2.7 μg kg− 1 min− 1 for the supine position group and 2.0 μg kg− 1 min− 1 for the tilt position group. The infusion rates were then adjusted using a fixed algorithm to maintain systolic blood pressure. The primary outcome was the pH of the umbilical artery.Results: Compared with tilt group, pH (supine group: 7.325 (7.29, 7.35) vs tilt group: 7.33 (7.3, 7.35), P = 0.76) and base excess (tilt group: − 0.98 (2.59) mM vs supine group: − 0.92 (2.77) mM, P = 0.9) of the umbilical artery are non-inferior. There was no difference in SBP (P = 0.16) or incidence of hypotension (P = 0.75) between the two groups. The incidence of reactive hypertension was greater in the supine position group (P < 0.001).Conclusion: If maternal blood pressure is maintained using the higher starting dose of metaraminol, the left tilted position may not be necessary among healthy patients (BMI less than 35 kg/m2) undergoing elective caesarean delivery with spinal anaesthesia.Keywords: Caesarean delivery, supine position, tilt position, metaraminol, noninferiority trial